Effect of Adding Kinesiotaping to Median Nerve Gliding Exercise Toward Hand Performance of Patients with Carpal Tunnel Syndrome by Using Michigan Hand Outcomes Questionnaire - Ratih Dwiratna Hakim; Kesoema, Tanti Ajoe; Rahmi Isma Asmara Putri; Endang Sri Mariani (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: CTS occurs due to local compression of the median nerve with manifestations of neuropathy, mostly in the productive population. Many conservative treatments have been observed to reduce the degree of pain and quality of life in CTS patients. Kinesiotaping is a new therapy that has been widely used for various musculoskeletal conditions and is known for reducing median nerve compression. Aim: To determine the effect of adding kinesiotaping to median nerve gliding exercise on hand function in CTS patients by using the Michigan Hand Outcomes Questionnaire. Methods: This research was an experimental randomized pre-and post-test group design. A sample of 24 patients from the Medical Rehabilitation Outpatient in RSUP Dr. Kariadi were divided into two groups randomly. The intervention group (n=12, dropout 1) got kinesiotaping application and median nerve gliding exercise. The control group (n=12, dropout 1) did the median nerve gliding exercise only. Hand performance has been evaluated before and at the end of the 4th week of treatment by using the Michigan Hand Outcomes Questionnaire. Result: There were significant improvements in the intervention group’s right-hand function (p<0,001), activities of daily living (ADLs) or the ability of the right hand to do certain tasks (p<0,001), work performance (p<0,001), pain (p=0,024), and satisfaction (p<0,001), as compared to the control group. Meanwhile, the intervention and the control group did not show significant differences in left-hand function score (p=0.884), left-hand ability score (p=0.884), and aesthetics score (p=1,000). Conclusion: There was a positive effect on improving hand performance in CTS patients by adding kinesiotaping to median nerve gliding exercises.